2011
DOI: 10.2341/1559-2863-36.1.119
|View full text |Cite
|
Sign up to set email alerts
|

Academy of Operative Dentistry Hollenback Memorial Prize

Abstract: has contributed more than 400 papers, research abstracts and book chapters related to all aspects of restorative dentistry. He has presented hundreds of lectures and continuing education courses in this country and abroad. He has also lectured for several annual meetings of the Academy of Operative Dentistry. His impact on the quality of patient care worldwide cannot be measured but is undoubtedly extremely significant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 0 publications
1
27
0
3
Order By: Relevance
“…The main cause of not using the rubber dam was that the asked persons consider it a time consuming procedure and they assume that it causes discomfort for the patient. These answers are similar to other reports, [14] although other studies that actually surveyed patients have found that patients acceptance is high when asked about the rubber dam [19,20].…”
Section: Discussionsupporting
confidence: 80%
“…The main cause of not using the rubber dam was that the asked persons consider it a time consuming procedure and they assume that it causes discomfort for the patient. These answers are similar to other reports, [14] although other studies that actually surveyed patients have found that patients acceptance is high when asked about the rubber dam [19,20].…”
Section: Discussionsupporting
confidence: 80%
“…Therefore, the null hypothesis was accepted for the class III composite fillings and rejected for the class IV fillings. Some studies have suggested that old composite fillings should be removed before teeth are restored with PLVs 1,13. Removing an old class III composite filling and replacing it with a ceramic veneer would result in a class IV cavity.…”
Section: Discussionmentioning
confidence: 99%
“…The rationale for this preparation was based on the recommendations in the literature to remove the existing filling and include the cavity in the final restoration 8,13. The final dimensions of the class IV cavity were set to 3 × 5 mm.…”
Section: Methodsmentioning
confidence: 99%
“…Generally, it is recommended that the resin composite should be cured in increments no greater than 2 mm in thickness. 21) However, cavity filling in very small increments may not be desirable due to increased chair time and inclusion of porosity between the layers. It is interesting to note that female dentists tend to split the layers into smaller increments in both class 2 and class 5 restorations.…”
Section: ⅳ Discussionmentioning
confidence: 99%